Stages of development of the art of Ziggurrat architecture in Mesopotamia: (Some examples taken) - Rukhsar Abdulghafoor Taha (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Architecture is one of the most important aspects of civilization in Mesopotamia, as the ancient architecture left us various buildings in their shapes, function, and building materials. Mesopotamia is characterized by extreme religiosity, so most of the antiquities discovered in Mesopotamia have a religious character, as high Ziggurrat were built in major cities, when the god descends from the geaven, he is in a state of fatigue, then he rests in a room built at the top of the Ziggurrat, just as many cities in southern Mesopotamia are sacred cities, such as, the city of Uruk, Ur, Nippur, Sibbar, Larsa, and Burseba… ect. This study is a field of research about the art of Ziggurrat architecture from the beginning to the last stages of development in Mesopotamia, Which goes through several stages and historical period. Ziggurrat is one attractive architectural phenomenon associated with temple building and religious center, appearing as an integral part of the temple building, in many cities in Mesopotamia there are several numbers of Ziggurrat. Of course, the appearance of the Ziggurrat building dates back to the end of the (Obaid period) the fourth millennium BC, it was simple in construction and built an a small layer, in later periods, it gradually developed from three layer until the last stage in the Neo-Babylonian period (Chaldean period) reached seven main layers, especially in terms of maps and architectural styles, in most Mesopotamian cities there were Ziggurrat, in some cities there were two or three Ziggurrat, each of which had a temple at the top dedicated to the main god of the city.